2009
DOI: 10.1016/j.placenta.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Human PlGF Gene Expression in Trophoblast and Nontrophoblast Cells by Oxygen Tension

Abstract: Objective-To determine the mechanism for differential effects of low oxygen tension on human PlGF gene transcription in trophoblast and nontrophoblast cells.Study Design-Human PlGF reporter clones and real time RT-PCR were used to compare the effects of hypoxia on gene transcription in human trophoblast and nontrophoblast cell lines. Overexpression of HIF-1α, inhibition of HIF-1 function and biochemical assessments of HIF-1 cofactor interactions were used to characterize hypoxia response mechanisms regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 43 publications
3
37
1
1
Order By: Relevance
“…No increase in histone acetylation was observed in promoter regions 4 and 5, where putative HREs, already reported by other authors, are present (not shown). 21,34 Surprisingly, a strong enrichment of H3 and H4 acetylation was instead observed in region 7, located in the second Plgf intron (P < 0.005 for histone H3 and P < 0.01 for histone H4, vs normoxic control) (Fig. 3B).…”
Section: Hypoxia Increases Plgf Expression In Huvec and H5v Cellsmentioning
confidence: 88%
See 1 more Smart Citation
“…No increase in histone acetylation was observed in promoter regions 4 and 5, where putative HREs, already reported by other authors, are present (not shown). 21,34 Surprisingly, a strong enrichment of H3 and H4 acetylation was instead observed in region 7, located in the second Plgf intron (P < 0.005 for histone H3 and P < 0.01 for histone H4, vs normoxic control) (Fig. 3B).…”
Section: Hypoxia Increases Plgf Expression In Huvec and H5v Cellsmentioning
confidence: 88%
“…We Despite several reports indicate that hypoxia, as well as the overexpression of HIF-1α, are responsible in vitro and in vivo for a positive modulation of PlGF, 2,25-29 the direct involvement of the HIF transcriptional complex has not been evidenced with classical transcriptional studies on Plgf promoter. 21,24,34 Considering that it has recently been reported that epigenetic regulation of chromatin structure plays an important role in defining the response to hypoxia, 30 we decided to investigate the role of epigenetic modifications, such as DNA methylation and histone acetylation, in the modulation of PlGF expression under hypoxic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The role of environmental conditions on PlGF expression in pregnancy is less clear. Upregulation of angiogenic factors, such as PlGF, in trophoblast seems not to be supported by hypoxia and hypoxia-induced factor-1α (14). As such, other regulatory pathways must be considered such as glucose availability, which might play a role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Placenta growth factor (PlGF) is a member of the vascular endothelial growth factor (VEGF) family [5][6][7][8][9] and plays important roles under physiological and pathological conditions. [10][11][12][13][14][15][16][17][18][19][20] We recently demonstrated that patients with SCD have elevated levels of PlGF and endothelin-1 (ET-1) and that enforced expression of PlGF in mice induces ET-1.…”
Section: Introductionmentioning
confidence: 99%